Pemberian Ekstrak Etanol Daun Jambu Mete (Anacardium occidentale) dalam Reduksi Kadar IL-6 dan Peningkatan Kadar SOD pada Mencit Fibrosis Hepar yang Diinduksi CCl4 - Hutabarat, Mariana Ruth Theresia; Hanifah, Fithria Nisa; Hadijah, Siti; Winarso, Djoko; Murwani, Sri (Jurnal Sain Veteriner, 2020)
Liver fibrosis is the excessive accumulation of extracellular matrix. The prevalence of liver fibrosis in small animal was reported by 10% of all systemic diseases occured in the United States. One of the toxic materials that cause liver fibrosis is carbon tetrachloride (CCl4). This study aims to determine the preventive effect of ethanol extract of leaves of cashew (Anacardium occidentale) against the production of Interleukin-6 (IL-6) and increase the levels of superoxide dismutase (SOD). Leaves cashew contain of flavonoids which have anti-inflammatory and antioxidant effects. This research is an experimental study, post-test control only design using a completely randomized design. Mice (Mus musculus) were divided into 5 groups, namely the negative control group, positive control group, preventive group dose of 500 mg/kg BW, 1000 mg/kg BW, and 1500 mg/kg BW. Interleukin-6 production is calculated using flowcytometry, while SOD was measured using spectophotometer. Data were statistically analyzed within one way ANOVA (Î±=0.05) with advanced test Post Hoc Tukey. Conclusions from this research that the preventive use of ethanol extract of leaves of cashew to prevent an increase of IL-6 production and increasing the levels of SOD in mice models of liver fibrosis. Production of IL-6 in group of 1500 mg/kg BW is 2.58%. SOD levels in group of 1500 mg/kg BW is 4.23%.Â